PENGEMBANGAN PEMBELAJARAN DEMONSTRASI TERBIMBING DENGAN STRATEGI DIFERENSIASI PADA MATA KULIAH MENGGAMBAR SKETSA - Muslim, Muslim; Diningrat, Raden Burhan Surya Nata; Islami, Dinul (Fakultas Bahasa dan Seni Universitas Negeri Medan, 2024)
This research is triggered by the low drawing skills of new students in the Department of Fine Arts Education at Unimed. Therefore, this study aims to develop a guided demonstration learning method with differentiation strategy in the Fine Arts Education Program. The approach used in this research is the Research and Development (R&D) method, utilizing the 4-D development model consisting of four main stages: defining, designing, developing, and disseminating. Data collection is carried out through questionnaire filling, observation, interviews, and sketch drawing assignments. Furthermore, samples are taken using purposive sampling technique. Data analysis is conducted using descriptive statistical analysis method with Likert scale. The research findings show that the average score of students' sketch drawing ability reaches 71.42%, categorized as